Factors Affecting Purchasing Decision on the Teak Products at Luang Prabang city, Luang Prabang Province: https://doi.org/10.69692/SUJMRD100429 - Bounsangar, Vongphachanh; YANGSANSAY, Chahue; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to investigate the situation of consumers purchasing teak products and decision to buy teak product in LuangPrabang. Using a questionnaire to gather data from a sample group of 380 individuals who have purchased teak products. And using the SPSS program to analyze the percentage of these consumers. The results of the study found that the situation when buying teak wood products is: ceiling edge 98.68%, ceiling wood 92.10%, kitchen cabinet 69.21%, chair 55.26%, table 54.73%, stairs 53.94%, bed 52.89%, plane wood 52.63%, door edge 47.36%, window frame 28.68%, door frame 26.31%, pillar wood 9.21%, air intake 6.57%, and finally sofa 4.73%. Expenses for more than 5 million kip cover 68.80%, 3 to 5 million cover 78.00%, 1 to 3 million cover 70.00%, and lower than 1 million kip cover 54.80%. 95% of buyers choose to buy in front of the store, 59% call to order for the store to pick up and deliver, and 49% order online. The study also found that 95% of the reasons are because rose wood or led wood is hard to find and the price is expensive; 65% of Luang Prabang is still plentiful of teak; there is a lot of teak wood; and teak wood is beautiful and lighter than other wood; and 35% because there is no choice. Result also found that the factors that making consumers decide to buy teak products are quality, appearance, easy to find and purchase, price and detail of the product with a statistical significance level of less than .05.